The Expansion of Merremia peltata (L.) Merrill in Fragmented Forest of Bukit Barisan Selatan National Park Enhanced by Its Ecophysiological Attributes - Yansen, Yansen; Wiryono, Wiryono; Deselina, Deselina; Hidayat, Muhammad F.; Depari, Efratenta K. (BIOTROPIA, 2015)
<!--[if gte mso 9]> 800x600 <![endif]--> <!--[if gte mso 9]> <![endif]--> <!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--> Forest opening and fragmentation may affect the composition of vegetation by permitting the expansion or domination of one or two species in the area.This study found that Merremia peltata, an invasive climbing/creeping species, has dominated some areas of Bukit Barisan Selatan National Park (BBSNP). Domination of this species was favoured by forest fragmentation, indicated by the significantly higher number of individuals of M. peltata in the open area than in intact forest. The ecophysiological characters of M. peltata support the ability of this species to become a strong invader. As the expansion of this species may negatively affect the biodiversity and vegetation health, the application of appropriate ecological approaches to control the domination of M. peltata in the conservation area is necessary. Â  Â  <!--[if gte mso 9]> Normal 0 false false false IN X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->